A Non-invasive Chromosome Screening Strategy for Prioritizing in vitro Fertilization Embryos for Implantation - Chen, Li; Sun, Qin; Xu, Juanjuan; Fu, Haiyan; Liu, Yuxiu; Yao, Yaxin; Lu, Sijia; Yao, Bing (Frontiers in Cell and Developmental Biology, 2021)
Preimplantation genetic testing for aneuploidy (PGT-A) are widely used to select embryos having normal ploidy for transfer, but they require invasive embryo biopsy procedure which may cause harm to the embryos and offspring. Therefore, a non-invasive approach to select embryos with normal ploidy for implantation is highly demanded. Non-invasive chromosome screening (NICS) methods have been proposed and applied in clinical practices but a large-scale validation versus invasive PGT and the whole embryo ploidy has not yet been reported. In this study, by using the whole embryo as a gold standard, we validated NICS assay in a total of 265 donated human embryos and compared its performance with conventional trophectoderm (TE) biopsy PGT. The NICS assay showed promising performance which is comparable to PGT-TE (sensitivity: 87.36% vs. 89.66%; specificity: 80.28% vs. 82.39%; NPV: 91.2% vs. 92.86; PPV: 73.08% vs. 75.73%). Additionally, NICS provides a scoring system for prioritizing embryo: embryos can be categorized into three groups with euploid prediction probabilities of 90.0%, 27.8%, and 72.2% for group euploid(A), aneuploid(B) and MAC(C) respectively. When an addition of TE assay is provided as a secondary validation, the accuracy significantly increases from 72.2% to 84.3% for group B and from 27.8% to 83.3% for group C. Our results suggest that NICS is a good rule in assay for identifying chromosomal normal embryos for transfer and might serve as a noninvasive approach for prioritizing embryos instead of preventing transfer of aneuploid and MAC embryos. It will help to ensure the safety of offspring and efficient utilization of embryos.